Transformación organizacional (2019)
The purpose of this monograph is to manage knowledge to the organizational transformation linked to different tools such as the critical success factors, competitive advantages and the most important part of the organizational climate, in order to make a continuous improvement from the management In this way, in this way, successful roles are provided to current organizations based on paradigms that are created with the needs of each organization, organizational transformation is the step that every organization must take to achieve success since to be more competitive an organization it is necessary to innovate not only internally "human management", but externally "strategically", the collaborators being the fundamental part for the progress of this change since the change of an organization depends on them.